Robot assistance in liver surgery: a real advantage over a fully laparoscopic approach? Results of a comparative bi‐institutional analysis. Issue 2 (21st March 2013) - Troisi, Roberto I.; Patriti, Alberto; Montalti, Roberto; Casciola, Luciano
Abstract Background Laparoscopic liver resection (LAPR) is safe and feasible with a better postoperative course as compared to open resections. Robot‐assisted liver surgery (ROBR) is a potential alternative to LAPR. In this study we compare outcomes between ROBR and LAPR. Methods Forty patients underwent ROBR and 223 LAPR for various indications. The surgical outcomes of two institutions, each with a specific advanced experience in laparoscopic and robotic surgery, were reviewed. Results The major hepatectomy rate was significantly higher in LAPR (16.6% vs 0%, p = 0.011) while a parenchyma‐preserving approach was favoured in ROBR (55% vs 34.1%, p = 0.019). More nodules were resected in the ROBR group (1.97 ± 1.4 vs 1.57 ± 1.1, p = 0.04). Overall conversion rate was 8/40 (20%) in the ROBR and 17/223 (7.6%) in the LAPR group (p = 0.034). Mean blood loss was 330 ± 303 ml and 174 ± 133 ml for the ROBR and LAPR groups, respectively (p = 0.001) Conclusions Despite higher conversion rates and blood loss, robot‐assisted surgery may allow the resection of more liver lesions, especially those located in the postero‐superior segments, facilitating parenchyma‐saving surgery with a comparable complication rate with respect to LAPR. Copyright © 2013 John Wiley & Sons, Ltd.